Surrogate Cerebrospinal Fluid Biomarkers for Assessing the Efficacy of Gene Therapy in Hurler Syndrome - Haseloff, Reiner F.; Trudel, Stephanie; Birke, Ramona; Schümann, Michael; Krause, Eberhard; Gomila, Cathy; Heard, Jean-Michel; Blasig, Ingolf E.; Ausseil, Jérôme (Frontiers in Neurology, 2021)
Mucopolysaccharidosis type I (MPS I) is caused by a deficiency of the lysosomal hydroxylase alpha-L-iduronidase (IDUA). The resulting accumulation of dermatan and heparan sulphate induces intellectual disabilities, premature death, and only few treatment options are available. In a previous study, we demonstrated the feasibility, safety and efficacy of gene therapy by injecting recombinant adeno-associated viral vector serotype (AAV)2/5-IDUA into the brain of a canine model of MPS I. We report on a quantitative proteomic analysis of control dogs and untreated dogs with MPS I cerebrospinal fluid (CSF) that had been collected throughout the study in the MPS I dogs. Mass spectrometry (MS) analysis identified numerous proteins present at altered levels in MPS I CSF samples. Quantitative immunoblotting, performed on CSF from healthy controls, untreated MPS I dogs, and MPS I dogs early-treated- and late-treated by gene therapy, confirmed the MS data for a subset of proteins with higher abundance (neuronal pentraxin 1, chitinase 3-like 1, monocyte differentiation antigen CD14, and insulin-like growth factor-binding protein 2). Scoring of the results shows that the expression levels of these proteins are close to those of the control group for dogs that underwent gene therapy early in life, but not for older treated animals. Our results disclose four novel predictive biomarker candidates that might be valuable in monitoring the course of the neurological disease in MPS patients at diagnosis, during clinical follow-up, and after treatment. Moreover, functions of the majority of upregulated proteins could suggest an involvement of the PI3K/AKT pathway in MPS-related processes.